To solve the equation represented by the model "2 x tiles = 1 x tile and 3 positive 1 tiles", we can break down the steps outlined:
-
Start with the equation: \[ 2x = 1x + 3 \]
-
Remove 1 x-tile from each side: \[ 2x - 1x = 1x - 1x + 3 \] This simplifies to: \[ x = 3 \]
-
Next, remove 3 unit tiles from the right side: Since there's no term on the left to remove from that side, the equation remains the same in this context.
-
Add 3 positive unit tiles to each side: \[ x + 3 = 3 \]
-
Arrange the tiles into equal groups to match the number of x-tiles: This means we can rewrite the equation if necessary, though it doesn't change since \( x = 3 \) has already been determined.
At every step, the operations maintain the equality of the equation. Consequently, the solution to the equation \( 2x = 3 + x \) is:
\[ \boxed{3} \]